Transport-Related Fringe Benefits - Jos van Ommeren; Arno van der Vlist; Peter Nijkamp (Tinbergen Institute, 2002)
Fringe benefits of various kinds have become an essential element of modern labour market mechanisms. Firms offer transport-related fringe benefits such as transport subsidies (company cars, travel and parking subsidies) and relocation subsidies to job applicants. The spatial implications of these fringe benefits have hardly received any systematic attention thus far. The present paper addresses this largely unexplored issue. Using information from a survey on firms' recruitment behaviour in the UK, this paper demonstrates that the applicants' journey-to-work time induces firms to offer various transport-related fringe benefits to job applicants. The implications of these transport-related fringe benefits for commuting and relocation are rather distinct. Transport subsidies discourage applicants, whereas relocation subsidies induce applicants to move closer to the workplace. We interpret the results as evidence that employers offer transport-related fringe benefits either to reduce the length of the journey to work or to compensate employees for the incurred commuting costs.
Keywords: J33; J41; R29; 330; fringe benefits; company car; residential mobility; Wohnungswechsel; Betriebliche Sozialleistungen; Großbritannien; Pendelverkehr